Local government service provision and non-payment within underdeveloped communities of the Johannesburg Unicity : service providers' and consumers' perspective - Netswera, Fulufhelo Godfrey (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DPhil)--University of Stellenbosch, 2005.